ICEQUAKES RECORDED AT SYOWA STATION, ANTARCTICA - カミヌマ, カツタダ; オカノ, ケンタ; KAMINUMA, Katsutada; OKANO, Kenta (National Institute of Polar Research, 1993)
P(論文) Icequakes have been recorded by a three-component seismograph of short period at Syowa Station (69°S, 39°E), Antarctica since seismic observations were started in 1966. The icequakes are roughly classified into two groups from their waveforms : a high frequency type and a low frequency type. Icequakes of the high frequency type occurred about 1.8 times more than those of the low frequency type during the 24 months from February 1990 to January 1992. In the monthly numbers, there are some swarms, however, in daily numbers, only one icequake swarm of low frequency type was observed. A big tremor was also recorded during the swarm. All icequakes and tremors appear to originate in the continental ice sheet. Seismic observations at Syowa Station seem to be useful to monitor ice sheet movement. departmental bulletin paper